Mutant p53 as a Regulator and Target of Autophagy - Shi, Yong; Norberg, Erik; Vakifahmetoglu-Norberg, Helin (Frontiers in Oncology, 2021)
One of the most notoriously altered genes in human cancer is the tumor-suppressor TP53, which is mutated with high frequency in more cancers than any other tumor suppressor gene. Beyond the loss of wild-type p53 functions, mutations in the TP53 gene often lead to the expression of full-length proteins with new malignant properties. Among the defined oncogenic functions of mutant p53 is its effect on cell metabolism and autophagy. Due to the importance of autophagy as a stress adaptive response, autophagy is frequently dysfunctional in human cancers. However, the role of p53 is enigmatic in autophagy regulation. While the complex action of the wild-type p53 on autophagy has extensively been described in literature, in this review, we focus on the conceivable role of distinct mutant p53 proteins in regulating different autophagic pathways and further discuss the available evidence suggesting a possible autophagy stimulatory role of mutant p53 in autophagy. Moreover, we describe the involvement of different autophagic pathways in targeting and degrading mutant p53 proteins, exploring the potential strategies of targeting mutant p53 in cancer by autophagy.